Os deslizamentos de sentido da palavra “cidadão” em meio a um Brasil em ebulição - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This final paper, throughout guided by a theoretical-methodological approach of a materialist aspect of Discourse Analysis, aims to comprehend how the production of meaning processes of the word citizen (cidadão) are developed in Brazil, observing distincts meanings this word could have in relation to the ideologies of those who use it. To achieve our objective, we chose, as object of analysis, brazilian official state documents which concerns to the meaning of being a citizen and to what type of citizen is intended to be produced in brazilian schools. The understanding of the notions of language, speech, meaning, ideology, unconsciousness, forgetfulness and discursive memory, are necessary for the realization of what this paper proposes. Besides that, seeking within the DA the approach of our analysis allows us a broad reflection on the conditions of production of a discourse, corroborating to reflect on the “effects of meaning” (PÊCHEUX, [1975] / 2009) produced. Thus, through our research, we realized that, if after the military dictatorship, the development of a conscious, reflective and social subject was sought, with the advent of neoliberal ideology in recent years, this sense shifted, approaching itself to the conception of a technical subject, prepared for the labor market.
Keywords: Discurso; Efeitos de sentido; Cidadãos; Discourse; Effects of meaning; Citizen; CNPQ::LINGUISTICA, LETRAS E ARTES